Das Pop. - Donna Beam Fine Art Gallery, University of Nevada, Las Vegas (Las Vegas : University of Nevada Las Vegas, 1995)
Allen, Joe ; Szafranski, David ; Hogg, Christopher ; Havel, Joseph ; Altman, Helen ; Bush, Martha
Das Pop, Donna Beam Fine Art Gallery, University of Nevada, Las Vegas, February 27 - March 31, 1995
boek